PHYSICAL CULTURE AS A MEANS OF PREVENTING POSTURAL DISORDERS IN YOUNG PEOPLE (SCIENCE TIME JOURNAL, 2026)
The article examines the problem of preventing posture disorders in young people through physical education. The relevance of the study is due to the increasing number of functional and structural disorders of the musculoskeletal system in students and schoolchildren, which is associated with hypodynamia, prolonged work at the computer, and non-compliance with hygiene standards. The aim of the work is to analyze the possibilities of physical culture as an effective means of preventing posture disorders and to develop practical recommendations for organizing classes. The article summarizes scientific approaches to preventing posture disorders and reveals the mechanisms by which physical exercises influence the formation of a correct posture. Research results indicate that systematic physical education sessions contribute to strengthening the muscular corset, developing motor skills, and reducing the risk of spinal deformities.